Editorial Note on the 1st NOvation Forum - Bagattolli, Carolina; Brandão, Tiago; Edwards-Schachter, Mónica; Hölsgens, Rick; Schubert, Cornelius (NOvation — Critical Studies of Innovation, 2021)
On September 15th till 17th 2021, scholars from all over the world met digitally to critically discuss various aspects of innovation, innovation research and innovation governance. The online forum was built up around three keynote speeches, a method lab led by Philippe Zittoun, and a paper and a theory lab, in which researchers presented their own research. The overarching theme of the online forum was Governance(s) of Innovation, which was discussed from various angles.